A study on the materials and supplies for paper conservation/preservation in selected countries in Southeast Asia and in Japan with implications to accessibility and sustainability - del Mar, Lulu J. (Animo Repository, 2015)
Preservation includes all the actions taken to retard deterioration of, or prevent damage to cultural materials including those of paper-based. An inevitable huge portion of our cultural heritage are in paper format (i.e. archives, books, manuscript, etc.), and the presence of these have posted the need to respond to various issues surrounding preservation of these cultural properties appropriately. When tackling issues in paper preservation, it is hard to eliminate the problems and challenges arising from the different techniques and practices, and supplies and materials. The focus of this study is to identify the different materials and supplies used for paper preservation in the Southeast Asian region including Japan, and to consider their accessibility and sustainability aspects for the development of paper preservation in the mentioned area. This study consolidates all preservation standards, techniques and practices for paper and manuscripts preservation in the Southeast Asian region including Japan, through qualitative-descriptive method and analysis: survey, observation and literature review. Based from this data, the common materials and supplies for paper preservation are consolidated, including their sources and suppliers. Analysis on their reliability, accessibility and sustainability were also done. From these analysis and outputs, the study provides a reference and guide for dealing with the issue of accessibility and sustainability on supplies and materials for paper preservation in the region. The study proposes a collaborative plan or consortium for Southeast Asian region including Japan on this area of preservation.